PENERAPAN STRATEGI PQ4R (PREVIEW, QUESTION, READ, REFLECT, RECITE, REVIEW) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 11 SOLOK SELATAN - Syahrial, Syahrial; Zulfaneti, Zulfaneti; Febriana, Rina (Pendidikan Matematika, 2014)
Â ABSTRACTÂ The background of This research is students understanding of mathematical concepts are still low, inactive, unwilling to issue an opinion, and do not want to ask one way around that is to implement a strategy PQ4R. This study aims to look at the activity in the learning of mathematics students and whether students understanding of mathematical concepts using PQ4R strategy better than the students understanding of mathematical concepts with conventional learning. This type of research is experimental research, the research design Against Random subject. The study population students of class VIII SMPN 11 South Solok academic year 2013/2014. Technique of random sampling, VIII.1 class was selected as the experimental class and the control class VIII.2. The instrument used in this study is the ultimate test of understanding of mathematical concepts and observation of student activity sheets. Form of the test used was obtained about the form of essays and reliable. The data analysis technique used is the t test of the party with the help of MINITAB software. Based on the analysis of data it is known that the two classes are normally distributed and homogeneous samples at significance level Î± = 0.05. Hypothesis test results obtained P-value = 0.001 less than the significance level Î± = 0.05, the research hypothesis is accepted so it can be concluded that the students understanding of mathematical concepts using PQ4R strategy better than the students understanding of mathematical concepts using conventional learning class VIII SMP 11 South Solok, at 95% confidence level .